Development of Cement-less Brick Using Microbes - Zainal Ariffin, Aina Farzana (Universiti Teknologi PETRONAS, 2017)
Concrete is produced globally each year because of highly demand in construction industry. Therefore, sustainability crisis is arisen because of numerous production of cement-based material that threatened the survivability of natural environment. One of the worrying situation that happened is the increasing of the air pollution due to the increasing of the usage of non-biodegradability. Releasing of carbon dioxide from cement manufacturing to the atmosphere is a serious environmental threat that lead to acceleration of global warming and climate changes. A feasible solution can be developed to overcome the environmental issue is by growing the bacteria and studying the effect of different concentration of bacteria and cementation media added to brick with the aim to determine the compressive strength of the brick. In presents the study, cement-less brick is developed by using bacteria which is acts as a replacement of cement.